Literasi dalam Pendidikan Islam - Aisyah, Siti (Journal of Islamic Education El Madani, 2023)
This paper discusses literacy in the perspective of Islamic Education. This discussion is important because so far literacy has only been understood as a reading skill and in the perspective of thought and discourse, it has not reached the essence of literacy, namely that from time to time, education is very, very necessary in the human journey. thus playing a major role in the revival of human spiritual life. In this process literacy is needed which in this context requires the ability to read up to the point of God's greatness, love for worship which is then demonstrated to the beauty of morality, which is the highest peak of literacy activity (iqra bismirobik). Why is that? because Islamic education directs all human beings to have good achievements in the course of their lives. Islamic education in this context plays a major role in "educating" humans so that their spiritual space is filled based on QS.al-Alaq verses 1-5.